Cooperation of the Shanghai Cooperation Organization in the Field of Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article describes the cooperation processes of the Shanghai Cooperation Organization in the field of education and the meetings held on this issue. The Shanghai Cooperation Organization also provides information about the Ministers of Education of the member States and the meetings in which they participated.